Conservation and improvement of native chicken: performance of fourth generation - Faruque, S; Bhuiyan, AKFH; Ali, Md Yousuf; Joy, ZF; Rashid, MA (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
Study was conducted at Bangladesh Livestock Research Institute, Savar, Dhaka with the objectives (i) to assess the performances of three Indigenous Chicken genotypes under intensive management, (ii) to select parental birds (males and females) and breed them in an assortative design for the production of fourth generation birds, and (iii) to estimate realized responses to selection to improve 3 Indigenous Chicken genotypes. A total of 1050-day-old chicks comprising of 3 types of chicken namely Naked Neck (NN), Hilly (H) and Non-descript Deshi (ND) were hatched in one batch for this study. In fourth generation (G4), selection was practiced at 40-week of age on the basis of an index comprising the parameters of age at first egg (AFE), body weight (BW), egg production (EP) and egg weight (EW). Improvement target of egg weight was to increase by 1g, egg production rate was to increase by 2 % per generation. The data were analyzed by factorial arrangement in a CRD by General Linear Model (GLM) Univariate Procedure in SPSS Computer Program. Day old chick weight was significantly (p<0.001) highest in H (32.73±0.60 g). Significant (p<0.001) body weight differences among the genotypes were observed at 4th , 8th and 12th weeks of age , with the highest body weight observed for H genotype (252.66±2.05, 674.68±6.41 and 1193.74±36.34g) than other two genotypes in all stages of age. H genotype (4.05 %) had non-significantly (χ2 = 0.775; p > 0.05) higher chick mortality than ND (3.10 %) and NN (2.92 %) genotypes at 0-8 weeks of age. The egg production up to 280 days was expected to increase by 3.34% for ND, 4.25% for H and 1.93% for NN, respectively. From the values obtained it was obvious that selection was effective in improving the percentage of egg production in three genotypes of chicken. The realized responses in terms of changes in breeding values in egg production and egg weight over generations were 0.722% and 5.349g, respectively. The negative genetic changes in age at first egg (-0.531 days) was in the expected direction. The realized response in age at first egg was found to decrease 0.531 days over two generations of selection. The realized response in the body weight at 40 weeks of age was found to be -0.001g due to selection over three generations. However, the results indicated that the genetic improvement for egg production in Indigenous Chicken will be effective through selection and breeding program. It may be concluded that the economic traits of Indigenous chicken could be improved in future generations through proper selection and planned mating. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 37-44